Upaya Penerapan Arti Penting Pernikahan Dan Cara Penyesuaian Antar Pasangan Di Kua Kecamatan Medan Perjuangan - Sonia Sonia; Atika Aulianda; Siti Azurah; Yulia Fathanah; Siti Sarah Aulia Husnah; Cindyan Cindyan; Uswatul Hasanah Siregar (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Marriage is one of Allah's commands to unite the perfection of worship performed by men and women to form a family that is sakinah, mawaddah and warrahma. Because by getting married, one can reduce sins and indecency from the public's eyes and protect oneself from adultery. This research is to discuss efforts in applying the importance of marriage and how to adjust between couples at the KUA Medan Perjuangan District, Jl. Education No.89. The research method uses a qualitative approach with a descriptive type, the source of which comes from informants and documents through data collection techniques of document analysis or documentation study. In a marriage, an adjustment is needed between husband and wife who have different characters. Failed adjustments usually end in divorce. Keywords: Efforts to Apply Meaning, Adjustment, and Patterns of Marriage.